Upaya Meningkatkan Hasil Belajar Geografi Melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD - Syamsuddin, Syamsuddin (Inspiratif Pendidikan, 2016)
This study was a Classroom Action Research) that aims to improve the learning achievement of Class XI IPS 1 students at SMAN 2 Pallangga in the geography lesson through STAD model. The subjects were the students of class XI IPS 1 at SMAN 2 Pallangga. The total numbers of learners were 20 students consisting of 12 females and 8 males in the academic year 2015/2016. This study was conducted in two cycles in which the both the cycles were conducted in 2 meetings. It was conducted in 2 months starting from October 5 until December 5, 2015. The findings showed that the students’ learning achievements in Geography lesson increased significantly both in the first and the second cycle. It was supported by the evidences that the level of students’ learning achievements in the first cycle (the first and the second meeting) were categorized as a medium with the average score of 65.95. Then, in the second cycle (the first and the second meeting), the students’ learning achievements were categorized as a high category with the average score of 75.25. Thus, STAD model can improve the students’ achievement in Geography lesson, both qualitatively and quantitatively. It can be seen in the tables and explanations in the attachment for in the first cycle and the second cycle from the first and second action I. Based on the findings stated previously, this model is totally effective applied in teaching especially on the subjects of geography because it can improve the students’ learning achievements both in doing their work in school and trying to provide opportunities for students to always try to do their learning activities. So, they can be more motivated to achieve maximum achievement based on the passing grade that has been determined.